ANALISIS KOMPILASI HUKUM ISLAM PASAL 84 TENTANG NUSYUZ ISTRI PERSPEKTIF MAZHAB HANAFI DAN MAZHAB SYAFI’I - rahmat ramadhan rahmat (Program Studi Perbandingan Mazhab, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2021)
In the Compilation of Islamic Law the issue of nusyuz is regulated in article 84, although there are rules regarding nusyuz in the KHI, there is no definite understanding of the problem of nusyuz, which in article 84 only regulates the issue of nusyuz from the wife's side. As for the meaning of the meaning of nusyuz itself, scholars have different opinions, including the opinion of Imam Shafi'i and Imam Hanafi. This type of research is library research (library research). The approach used is descriptive analytic. The data collection technique used in this research is library research. The method used is